2018
DOI: 10.1002/jmv.25247
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rotavirus‐ and norovirus‐specific IgG memory B cells in tonsils

Abstract: Because rotavirus (RV) and norovirus (NoV) are transmitted through the fecal-oral route, tonsils due to their location within the oropharynx may sample or become infected with these viruses. We investigated if RV and NoV RNA/antigen, or virus-specific memory/plasma B cells can be detected in the tonsils. While neither RV/NoV antigen, nor genomic RNA was detected, 90% (27/30) of tonsils tested had RV- and NoV-specific IgG memory B cells. However, the mechanism explaining how these cells get there (whether becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Of interest, two recent studies have detected diarrheal viruses, including HuNoV, in the nasopharynx of 11.4% [39] and 15.8% [40] of children with acute gastroenteritis, and a prevalence of 0.5% has also been reported for HuNoV RNA in respiratory secretions of children with influenza-like illness [41]. An independent study on subjects without acute gastroenteritis found HuNoV-specific memory B cells in tonsils [42], although they could not detect any marker of viral replication and they did not explore the origin or the role of these cells in that tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, two recent studies have detected diarrheal viruses, including HuNoV, in the nasopharynx of 11.4% [39] and 15.8% [40] of children with acute gastroenteritis, and a prevalence of 0.5% has also been reported for HuNoV RNA in respiratory secretions of children with influenza-like illness [41]. An independent study on subjects without acute gastroenteritis found HuNoV-specific memory B cells in tonsils [42], although they could not detect any marker of viral replication and they did not explore the origin or the role of these cells in that tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro stimulation strategy is well suited for analysis of lymphoid tissue−resident MBC populations, but limited work has been done to establish protocols that are optimal for unfractionated lymphoid tissue cells (Cao et al, 2010). Tonsillar cell suspensions have been stimulated with a PWM/SAC/CpG cocktail for IgG MBC analysis (Sharma et al, 2019), and our preliminary experiments suggest that R848/IL-2/IL-10 is effective for stimulating IgG MBCs in splenocyte preparations.…”
Section: Commentary Background Informationmentioning
confidence: 98%